2020
DOI: 10.1111/ppl.13063
|View full text |Cite
|
Sign up to set email alerts
|

WEG1, which encodes a cell wall hydroxyproline‐rich glycoprotein, is essential for parental root elongation controlling lateral root formation in rice

Abstract: Lateral roots (LRs) determine the overall root system architecture, thus enabling plants to efficiently explore their underground environment for water and nutrients. However, the mechanisms regulating LR development are poorly understood in monocotyledonous plants. We characterized a rice mutant, wavy root elongation growth 1 (weg1), that produced higher number of long and thick LRs (L‐type LRs) formed from the curvatures of its wavy parental roots caused by asymmetric cell growth in the elongation zone. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…For RDW, we detected two co-located MQTLs including MQTL-RDW1 and RDW2 co-locating with OsMGT1 and OsAIR1 genes, respectively. Additionally, WEG1 at MQTL-RDW5 is a novel gene that regulates root related traits 85 and may keep the same role under water deficit conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For RDW, we detected two co-located MQTLs including MQTL-RDW1 and RDW2 co-locating with OsMGT1 and OsAIR1 genes, respectively. Additionally, WEG1 at MQTL-RDW5 is a novel gene that regulates root related traits 85 and may keep the same role under water deficit conditions.…”
Section: Resultsmentioning
confidence: 99%
“…no. (genomic position in Mb) Maize MQTL reference Ortho-MQTL-PH7 MQTL-PH7 4 (30.86–31.61) mQTL_PEH_10 10 (142.39–143.64) 85 MQTL-YLD2 2 (26.47–27.59) mQTL_GY_5 5 (196.85–199.69) 84 Ortho-MQTL-YLD2 MQTL5.7 5 (199.95–200.82) 16 Ortho-MQTL-YLD3 MQTL-YLD3 3 (29.58–30.36) mQTL_GY_1b 1 (276.04–279.33) 84 Ortho-MQTL-YLD4 MQTL-YLD4 4 (29.15–30.82) mQTL_GY_10b 10 (135.81–142.38) 84 Ortho-MQTL-YLD6 MQTL-YLD6 8 (0.26–0.71) MQTL6.1 6 (1.58–3.65) 16
Figure 4 Comparative maps of ortho-MQTLs between rice and maize. ( A ) ortho-MQTL-PH7, ( B ) ortho-MQTL-YLD2, ( C ) ortho-MQTL-YLD3, ( D ) ortho-MQTL-YLD4 and ( E ) ortho-MQTL-YLD6.
…”
Section: Resultsmentioning
confidence: 99%
“…Gravitropic curvature upregulates auxin signaling in rice and induces L-type lateral root formation on the convex side (Lucob-Agustin et al 2020b). Additionally, weg1 mutants that showed wavy parental roots, including in the seminal and crown roots, and exhibited L-type lateral roots arising from the curvatures of the parental roots, revealed that wavy parental roots are important in increasing the frequency of L-type lateral roots through the non-canonical pathway (Lucob-Agustin et al 2020b).…”
Section: Previewmentioning
confidence: 98%
“…Vegetative and reproductive SAMs were isolated by hand dissection of the basal region of rice under a microscope 31 . Generation of the transgenic lines OsMADS15-mOragene and DR5rev:NLS-3xVenus was previously reported 22,32 .…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%